Outcomes of lung transplantation from organ donation after medical assistance in dying: First North American experience. Issue 6 (7th March 2022) - Watanabe, Tatsuaki; Kawashima, Mitsuaki; Kohno, Mikihiro; Yeung, Jonathan; Downar, James; Healey, Andrew; Martinu, Tereza; Aversa, Meghan; Donahoe, Laura; Pierre, Andrew; de Perrot, Marc; Yasufuku, Kazuhiro; et al.
Abstract : Over 2.5% of deaths in Canada occur as a result from medical assisting in dying (MAID), and a subset of these deaths result in organ donation. However, detailed outcomes of lung transplant recipients using these donors is lacking. This is a retrospective single center cohort study comparing lung transplantation outcomes after donation using MAID donors compared to neurologically determined death and controlled donation after circulatory death (NDD/cDCD) donors from February 2018 to July 2021. Thirty‐three patients received lungs from MAID donors, and 560 patients received lungs from NDD/cDCD donors. The donor diagnoses leading to MAID provision were degenerative neurological diseases ( n  = 33) and end stage organ failure ( n  = 5). MAID donors were significantly older than NDD/cDCD donors (56 [IQR 49–64] years vs. 48 [32–59]; p  = .0009). Median ventilation period and 30 day mortality were not significantly different between MAID and NDD/cDCD lungs recipients (ventilation: 1 day [1–3] vs 2 days [1–3]; p  = .37, deaths 0% [0/33] vs. 2% [11/560], p  = .99 respectively). Intermediate‐term outcomes were also similar. In summary, for lung transplantation using donors after MAID, recipient outcomes were excellent. Therefore, where this practice is permitted, donation after MAID should be strongly considered for lung transplantation as a way to respect donor wishes while substantially improving outcomes for recipients with end‐stage lung disease. Abstract : The first North American experience transplanting lungs from donors who donated after medical assistance in dying reports excellent outcomes.